2004
DOI: 10.1213/01.ane.0000133580.54026.65
|View full text |Cite
|
Sign up to set email alerts
|

Small-Dose Intrathecal Clonidine and Isobaric Bupivacaine for Orthopedic Surgery: A Dose-Response Study

Abstract: We examined the dose-response relationship of intrathecal clonidine at small doses ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
120
3
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(156 citation statements)
references
References 29 publications
28
120
3
5
Order By: Relevance
“…Similar results were also observed by Strebel et al and Gecaj-Gashi et al . 10,11 This was also in accordance to the study of Tilker et al who also reported that the time taken for regression of sensory block was statistically more in patients of clonidine group. 12 Gupta K et al compared the analgesic efficacy of intrathecal clonidine, 30 µg with butorphanol 0.20 mg during orthopedic surgeries.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were also observed by Strebel et al and Gecaj-Gashi et al . 10,11 This was also in accordance to the study of Tilker et al who also reported that the time taken for regression of sensory block was statistically more in patients of clonidine group. 12 Gupta K et al compared the analgesic efficacy of intrathecal clonidine, 30 µg with butorphanol 0.20 mg during orthopedic surgeries.…”
Section: Discussionsupporting
confidence: 90%
“…readings remained above the critical value of 65 mmHg at majority of times. These findings agree with other investigators demonstrating a decrease in arterial BP even with lower doses (15-150 g) of clonidine and relative hemodynamic stability with administration of larger doses [5,6,8,20,24] . Some authors argued that the hypotensive effects of clonidine at lower dose can be because of low dose of Bupivacaine used in those studies.…”
Section: Discussionsupporting
confidence: 93%
“…VAS scores were significantly lesser with combination (BC-150<BC-75< B). Our study results were similar to Baker [19] , Strebel et al [20] , Grandhe [15] , Sethi et al [1] , Filos KS (1994) [21] , Mercier F J (1998) [22] and Chiari et al (1999) [23] .…”
Section: Discussionsupporting
confidence: 91%
“…Grace et al, however observed prolonged time to onset of motor block in pethidine-clonidine group which is in contrast to the results of our study. 25 The difference in the result could be due to the fact that higher doses of pethidine 0.75 mg/kg was used in this study. It is possible that the higher dose of intrathecal pethidine could mask the effect of intrathecal clonidine.…”
Section: Discussionmentioning
confidence: 83%